2020
DOI: 10.5847/wjem.j.1920-8642.2020.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and prognosis of community-acquired pneumonia in autoimmune disease-induced immunocompromised host: A retrospective observational study

Abstract: BACKGROUND: Community-acquired pneumonia (CAP) in autoimmune diseases (AID)-induced immunocompromised host (ICH) had a high incidence and poor prognosis. However, only a few studies had determined the clinical characteristics of these patients. Our study was to explore the characteristics and predictors of mortality in CAP patients accompanied with AID-induced ICH. METHODS: From 2013 to 2018, a total of 94 CAP patients accompanied with AID-induced ICH, admitted to Emergency Department of Zhongshan Hospital, Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Therefore, NLR and PLR are considered to be representative of the inflammatory status [ 17 , 18 ]. It has been reported that NLR and PLR may be alternative markers of CAP-related inflammation [ 19 , 20 , 21 ]. Moreover, NLR and PLR have been shown to be predictors of CAP severity [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, NLR and PLR are considered to be representative of the inflammatory status [ 17 , 18 ]. It has been reported that NLR and PLR may be alternative markers of CAP-related inflammation [ 19 , 20 , 21 ]. Moreover, NLR and PLR have been shown to be predictors of CAP severity [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our analysis, LDH was the only marker that significantly predicted all three measured outcomes: ICU admission, ARDS and mortality. LDH is released from cells upon damage to their cytoplasmic membrane, and is not only a metabolic but also an immune surveillance prognostic biomarker [22,23]. LDH increases the production of lactate, which leads to enhancement of immune-suppressive cells and inhibition of cytolytic cells [24].…”
Section: Efficacy Of Corticosteroidsmentioning
confidence: 99%
“…[10] Elevated APACHE IV score indicates an association between critical condition and mortality, and APACHE score has been found as a risk factor for the prognosis of different critical populations in ICU. [44,45] Older patients who require prolonged ventilation have a higher risk of mortality and heavier burdens of treatment. [24,46] Also, for patients older than 70 years, they have been found to have an increased risk of death due to sepsis.…”
Section: Discussionmentioning
confidence: 99%